Spatial and social aspects of the housing policies for refugees and immigrants in Greece: a critical overview - Gemenetzi, Georgia; Papageorgiou, Marilena (The Greek Review of Social Research, 2017)
The paper critically assesses the housing policies adopted in the 1920s and 1990s as well as the housing rehabilitation adopted for the new-coming refugee and immigrant populations. Considering the experiences of the past, it is deduced that housing policy for the new-coming populations have to endorse the following principles in order to be beneficial to the national economy and society: a) rational geographical distribution of the newcoming populations according to spatial criteria and their personal needs and skills, b) housing rehabilitation in the framework of an integrated urban planning, c) dispersion within the social and urban fabric via social rental housing.